UHPLC-MS Metabolomic Fingerprinting, Antioxidant, and Enzyme Inhibition Activities of Himantormia lugubris from Antarctica - Carlos Areche; Javier Romero Parra; Beatriz Sepulveda; Olimpo García-Beltrán; Mario J. Simirgiotis (Metabolites, 2022)
Himantormia lugubris is a Chilean native small lichen shrub growing in the Antarctica region. In this study, the metabolite fingerprinting and the antioxidant and enzyme inhibitory potential from this species and its four major isolated compounds were investigated for the first time. Using ultra-high performance liquid chromatography coupled to quadrupole-Orbitrap mass spectrometry analysis (UHPLC-Q-Orbitrap-MS), several metabolites were identified including specific compounds as chemotaxonomical markers, while major metabolites were quantified in this species. A good inhibition activity against cholinesterase (acetylcholinesterase (AChE) IC50: 12.38 ± 0.09 µg/mL, butyrylcholinesterase (BChE) IC50: 31.54 ± 0.20 µg/mL) and tyrosinase (22.32 ± 0.21 µg/mL) enzymes of the alcoholic extract and the main compounds (IC50: 28.82 ± 0.10 µg/mL, 36.43 ± 0.08 µg/mL, and 7.25 ± 0.18 µg/mL, respectively, for the most active phenolic atranol) was found. The extract showed a total phenolic content of 47.4 + 0.0 mg of gallic acid equivalents/g. In addition, antioxidant activity was assessed using bleaching of DPPH and ORAC (IC50: 75.3 ± 0.02 µg/mL and 32.7 ± 0.7 μmol Trolox/g lichen, respectively) and FRAP (27.8 ± 0.0 μmol Trolox equivalent/g) experiments. The findings suggest that H. lugubris is a rich source of bioactive compounds with potentiality in the prevention of neurodegenerative or noncommunicable chronic diseases.